Solutions Improving the SMES’ Exporting Activities in Southern Area of Vietnam - Thu Thuy and Phan Thanh Tam, Le (British Journal of Marketing Studies, 2017)
According to the objective of the project to raise the competitiveness of Vietnam's export commodities up to 2020, the orientation to 2030 has been approved by the Prime Minister on 03/8/2017. Export commodities striving to increase by 2020 gradually; the share of agricultural and aquacultural exports in developed markets such as the EU, Japan and South Korea will increase. At the same time, export commodities strive to achieve an average commodity export growth rate of 8% per year in the period 2016-2020 and an average of 9% -10% per year in the period 2021-2030. This paper objective is to find some solutions improve the efficiency of exports to the world market in the coming time. The research results showed that there were 200 managers of SMEs related to Southern Area of Vietnam who interviewed and answered about 21 questions but 188 managers of SMEs processed. Data collected from 8/2016 to 11/2017 for the managers of SMEs of Southern Area of Vietnam. The paper had been analyzed five factors affecting the SMEs’ exporting activities of Southern Area of Vietnam with significance level 5 percent. Solutions are recommended for improving the SMEs’ exporting activities in Southern Area of Vietnam.